2005
DOI: 10.1007/s00425-005-0071-5
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of drought-related trehalose 6-phosphate-synthase gene from cultivated cotton (Gossypium hirsutum L.)

Abstract: Due to the important role of cotton drought-tolerant varieties and the reported involvement in this trait of trehalose-6-phosphate-synthase, the respective gene (TPS) was isolated and characterized from cultivated cotton, Gossypium hirsutum (ZETA 2 cultivar), using a chromosome-walking technique. TPS has three exons comprising the coding region. Southern blot analysis indicated that the Gossypium genomes (A and D) contain a single copy of TPS per genome. In addition, the expression of this gene was studied in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
45
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 45 publications
1
45
0
Order By: Relevance
“…Trehalose accumulation in response to water stress in wheat was associated with a decrease in trehalase activity (El-Bashiti et al, 2005;Kosmas et al, 2006). However, trehalose levels were still relatively low and unlikely to make much contribution to osmoregulation unless very localized.…”
Section: Tre6p and Abiotic Stress Tolerancementioning
confidence: 99%
“…Trehalose accumulation in response to water stress in wheat was associated with a decrease in trehalase activity (El-Bashiti et al, 2005;Kosmas et al, 2006). However, trehalose levels were still relatively low and unlikely to make much contribution to osmoregulation unless very localized.…”
Section: Tre6p and Abiotic Stress Tolerancementioning
confidence: 99%
“…Capacity to produce trehalose, earlier thought to be absent from higher plants, has now been reported to accumulate in high amounts in some drought-tolerant ferns, the resurrection plant Selaginella lepidophylla (Penna, 2003) and desiccation-tolerant angiosperm Myrothamnus flabellifolia (Drennan et al, 1993). The presence of low amounts of trehalose was demonstrated even in tobacco (Goddijn et al, 1997) and many higher plants (Kosmas et al, 2006). Its metabolism may be channelized to enhance drought tolerance in plants ( Pilon-Smits et al, 1998;Penna, 2003).…”
Section: Compatible Solutes and Osmotic Adjustmentmentioning
confidence: 99%
“…This probable high number of isoforms of TPS in sugarcane may be due to the polyploidy and the hybrid condition associated to the Saccharum spp. As well as in sugarcane, transcripts of TPS genes in several plant tissues like in Arabidopsis [8,12], rice [33] and maize [34] were found. The in silico expression indicates a constitutive expression of TPS genes in several tissues and treatment approaches in the hibrid sugarcane plants.…”
Section: Tps In Silico Expressionmentioning
confidence: 99%
“…Arabidopsis thaliana [8][9][10], rice, potato [11] and cotton [12]. Leyman et al [9] found 11 similar TPS genes presumably functional in the genome of Arabidopsis.…”
mentioning
confidence: 99%
See 1 more Smart Citation